Review of the Concept of wu wei (无为): Its Relationship with Anarchism and Soft Power - Hernández, Emilio (Sinología hispánica. China Studies Review, 2018)
Through the analysis of different classical texts of Chinese literature, this article aims to carry out a review of the Taoist concept of wu wei and to make an approximation to the relationship between Taoism’s political conception and current anarchism. The article discusses, also from this review, the links between basic behavior and Taoist attitude and leadership and the concept of soft power that govern international relations today. Getting to understand and internalize the definition and principles of leadership wu wei, could help society to form leaders who face and manage conflicts better: with more reflection and patience and achieve, with a Taoist leadership management, of its strength and of its soft power, a more balanced and harmonious world.